Mechanical Analyses of Quadriceps Tendon Graft with Five Different Fixation Techniques on the Femoral Side: an Experimental Study on Sheep Knees - Çetin, M; Söylemez, M. S; Öztürk, B. Y; Mutlu, I; Karakuş, Ö (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2022)
PURPOSE OF THE STUDY We aimed to evaluate the biomechanical properties of quadriceps tendon graft with a bone plug ending (QTBP) and a quadriceps graft with a tendinous ending(QTT) fixed on the femoral side with different fixation devices. MATERIAL AND METHODS Twenty-five paired 2-year-old calf QTs and 25 paired 2-year-old sheep femurs were used for this study. 90x8 mm central part of the quadriceps tendons with or without a bone plug was harvested. 8×25 mm tunnel was placed in lateral condyles. The QTT was fixed with four different fixation devices, including the adjustable suspensory system (QTT-ASS, group 1), biodegradable interference screws (QTT-BIS, group 2), titanium interference screws (QTT-TIS, group 3), and an adjustable suspensory system + biodegradable interference screws (QTT-(ASS+BIS), group 4); QTBP was fixed with titanium interference screws (QTBP-TIS, group 5). All groups were tested in a servohydraulic materials testing machine. Stiffness(N/mm), slippage of the tendon(mm), and the ultimate tensile load-bearing ability(N) of the groups were tested. The Kruskal-Wallis H test was used with the Monte Carlo simulation technique to compare the nonparametric variables of stiffness, slippage, and ultimate tensile load. Dunn's test was used for the post hoc analyses. RESULTS Group 3 had the stiffest fixation (median 45.09 N/mm). The amount of slippage was highest in group 1(median 6.41mm). Group 1 was the most resistant group against a tensile load during the load-to-failure test(464 N). Fixing the QTT with the ASS and BIS in group 4 increased both stiffness and ultimate tensile load strength. There was no significant difference between the QTBP and QTT fixed with titanium screws. Fixing QTT with titanium screws was significantly superior to fixation with BIS(p < 0.05). CONCLUSIONS This study demonstrates that QTBP fixation with TIS have no advantage over QTT fixation with TIS on the femoral side. Although the QTT group fixed with ASS was the most resistant group against tensile forces during load-to-failure test, amount of slippage was highest for this group as well. Thus, if an ASS is to be used, a strong tension force must be applied prior to tibial side fixation to prevent further slippage of the graft in the tunnel. Key words: anterior cruciate ligament, quadriceps tendon graft, femoral side, fixation, biomechanical properties.
Keywords: titan; šlachy; Titanium; biomechanika; kostní šrouby; Biomechanical Phenomena; Animals; Equidae; ovce; Sheep; zvířata; Tendons; Bone Screws